Description of The Psychological Condition of Adolescents With Social Problems and Bullying - setya; Erriza Farizan Adani (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Dysfunctional families and experiences of bullying can contribute to social problems and emotional instability in adolescents. This article analyzes the psychological condition of a 16 year old adolescent who exhibits withdrawal, self-harming behaviors, and suicidal ideation, exacerbated by conflicts with their mother and the infedelity of a stepfather. The research employs a qualitative approach with a case study analysis, referencing Karen Horney’s psychoanalytic theory, which emphasizes the importance of interpersonal relationships and the fulfillment of basic psychological needs. Data were collected through interviews, observations, and psychological tests, indicating that the subject struggles to build healthy social relationships, along with feelings of inferiority and helplessness. The results show that dissatisfaction with the ideal self-image and traumatic experiences contribute to self-harming behaviors and suicidal tendencies. These findings highlight the importance of social support and emotional understanding in adolescent psychological development, as well as the need for interventions to address the negative impacts of family environments and bullying. This research provides insights into how these factors interact and affect individual mental health.